Spatial and temporal variations of screening for breast and colorectal cancer in the United States, 2008 to 2012. Issue 51 (December 2016) - Feng, Xue; Tan, Xi; Alenzi, Ebtihag O.; Rai, Pragya; Chang, Jongwha
Abstract : Abstract: Cancer screening tests are important tools to combat cancer-related morbidity and mortality. There is limited up-to-date research on spatial and temporal variations of colorectal and breast cancer screening in the United States. County-level data of cancer screening adherence rates were generated from 2008 to 2012 Behavioral Risk Factor Surveillance System. We performed the univariate local indicators for spatial analyses (LISA) for the geographic differences of screening adherence rate and the differential LISA for the change of screening adherence rate from 2008 to 2012. In the univariate LISA, low-to-low clusters were consistently identified in counties of New Mexico, Wyoming, and Mississippi ( P < 0.05) for both screenings. In the differential LISA, we found low-to-low clusters in Indiana counties ( P < 0.05) for mammography screening, which implied that counties with a below-average difference in mammography adherence were surrounded by counties of below-average difference in adherence rates. A high-to-high cluster was also identified in the southern Appalachian counties for mammography screening ( P < 0.05). No obvious spatial pattern was found for the colorectal cancer screening adherence rate across the United States. We found low-to-low clusters over time in adherence to screening guidelines for both cancer types in New Mexico, Wyoming, and Mississippi, and clusters of potential decrease in adherence to mammography screening guideline in counties of Indiana. The study also showed improvement on mammography screening clustered in southern Appalachia. The methodology adopted in this study identified areas with clusters of consistent low adherence to screening and a decrease in adherence, which implies that further research and intervention is warranted. Abstract : Supplemental Digital Content is available in the text